PENGEMBANGAN ALAT PERAGA LOGIKA MATEMATIKA MINIATUR TANDON AIR TINGKAT TIGA MELALUI REALISTIC MATHEMATICS EDUCATION (RME) - Septia Ezy Pratama; Yahya AD; Dona Dinda Pratiwi (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This study aims to develop mathematical logic teaching aids through realistic mathematics education that is feasible, valid and effective so that students can find knowledge directly. This type of research is development research (Reseacrh and Development / R&D) with the ADDIE development model with subjects namely mathematics education students at UIN Raden Intan Lampung. The research data was obtained by interview techniques and questionnaires. The results of the study show that the props developed by the researcher in the form of this application have been declared valid by experts who test the material aspects and aspects of the media; declared interesting based on research on small group trials by 3 students and also 10 students in a large group trial by purposive sampling; and has effectiveness in the high category based on the results of field tests in 1 class of students who have just taken a mathematics logic course.